Interfacing the Hebrew Bible: past, present and future applications for the BHSA - Winther-Nielsen, Nicolai (HIPHIL Novum, 2019)
The open and constantly evolving BHSA database text of the Hebrew Bible (Biblia Hebraica Stuttgartensia Amstelodamensis) from the Eep Talstra Centre for Bible and Computer has amazing potential for past, present and future projects in Biblical Hebrew linguistics, language learning and interpretation. The BHSA was used 2004-2009 in the Role Lexical Module http://lex.qwirx.com/lex/clause.jsp in order to provide an interface for bidirectional mapping between morpho-syntax and semantics for linguists working within the Role and Reference Grammar model. Since then the BHSA har been used for educational purposes in the corpus-driven learning environment Bible Online Learner offering a persuasive interface for enquiry and practice in and with the BHSA text. Based on these applications for linguistic research and persuasive language learning, we now have a better idea of how the next generation of interfaces for the Hebrew Bible should be designed. We may even envision the direction to take for the next 5 years from now. For translation and education, we will need glosses for many languages, scaffolding with interactive archaeological, textual, grammatical and interpretive data, auralreading and much more.